Household Transmission of Pandemic (H1N1) 2009, San Antonio, Texas, USA, April–May 2009 - Oliver W. Morgan; Sharyn Parks; Trudi Shim; Patricia A. Blevins; Pauline M. Lucas; Roger Sanchez; Nancy Walea; Fleetwood Loustalot; Mark R. Duffy; Matthew J. Shim; Sandra Guerra; Fernando Guerra; et al. (Emerging Infectious Diseases, 2010)
To assess household transmission of pandemic (H1N1) 2009 in San Antonio, Texas, USA, during April 15–May 8, 2009, we investigated 77 households. The index case-patient was defined as the household member with the earliest onset date of symptoms of acute respiratory infection (ARI), influenza-like illness (ILI), or laboratory-confirmed pandemic (H1N1) 2009. Median interval between illness onset in index and secondary case-patients was 4 days (range 1–9 days); the index case-patient was likely to be <18 years of age (p = 0.034). The secondary attack rate was 4% for pandemic (H1N1) 2009, 9% for ILI, and 13% for ARI. The secondary attack rate was highest for children <5 years of age (8%–19%) and lowest for adults >50 years of age (4%–12%). Early in the outbreak, household transmission primarily occurred from children to other household members and was lower than the transmission rate for seasonal influenza.